2008
DOI: 10.1093/carcin/bgn142
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and clinical studies of cancer chemoprevention by antioxidants in berries

Abstract: Reactive oxygen species (ROS) are a major cause of cellular injury in an increasing number of diseases, including cancer. Most ROS are created in the cell through normal cellular metabolism. They can be produced by environmental insults such as ultraviolet light and toxic chemicals, as well as by the inflammatory process. Interception of ROS or limiting their cellular effects is a major role of antioxidants. Due to their content of phenolic and flavonoid compounds, berries exhibit high antioxidant potential, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
140
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 73 publications
0
140
0
2
Order By: Relevance
“…Phenolic compounds are considered as the main contributor to antioxidant activity in plant extracts due to their higher value in total phenolic content (Hodzic et al 2009). The polyphenol antioxidant capacity has been taken into account as one of the outstanding mechanisms of action in inhibiting mutagenesis and cancer initiation, by means of their capacity to scavenge ROS, activate antioxidant enzymes, prevent carcinogen-induced DNA adduct formation, enhance DNA repair, and reduce overall oxidative DNA injury (Stoner et al 2008). The flavonoids content in ME, EE and BE varied from 3.7 to 64.3, 3.7 to 84.8 and 10.4 to 278.9 mg QE/100 g (dwb) respectively and it differed significantly (P < 0.05) among all the vegetables in their respective extracts.…”
Section: Quantitative Testing Of Phytochemicalsmentioning
confidence: 99%
“…Phenolic compounds are considered as the main contributor to antioxidant activity in plant extracts due to their higher value in total phenolic content (Hodzic et al 2009). The polyphenol antioxidant capacity has been taken into account as one of the outstanding mechanisms of action in inhibiting mutagenesis and cancer initiation, by means of their capacity to scavenge ROS, activate antioxidant enzymes, prevent carcinogen-induced DNA adduct formation, enhance DNA repair, and reduce overall oxidative DNA injury (Stoner et al 2008). The flavonoids content in ME, EE and BE varied from 3.7 to 64.3, 3.7 to 84.8 and 10.4 to 278.9 mg QE/100 g (dwb) respectively and it differed significantly (P < 0.05) among all the vegetables in their respective extracts.…”
Section: Quantitative Testing Of Phytochemicalsmentioning
confidence: 99%
“…Today, growers in Oregon, the leading production region, typically see a decline in production after the second harvest and remove fields after only three or four seasons because of decreased profitability (Halgren et al 2007). At the same time, demand for black raspberry fruit has increased in recent years in large part because of studies outlining the potential health benefits of black raspberry consumption (Kresty et al 2001;Seeram et al 2006;Seeram 2008;Stoner et al 2005Stoner et al , 2008. These factors have combined to create a renewed interest in breeding better cultivars that meet the demands of growers and consumers.…”
mentioning
confidence: 99%
“…The first are oxindole alkaloids, initially studied and described in 1967; the second are a set of molecules know as Carboxy Alkyl Esters (CAEs ™) first identified and described in 1997 as the bioactive ingredients in AC-11® (Reviewed in Pero 2010b). More recently in 2005 (Sheng et al 2005) it was shown that one of the acid moieties of CAEs is quinic acid, and it is now documented to be one of the more effective DNA repair ingredients found in Uncaria spp, or brightly-colored berry extracts that also contain quinic acid (Stoner et al 2008, Pero 2006, and in turn can enhance DNA repair. It is important to remember that quinic acid is a natural-occurring alpha hydroxy organic acid quite ubiquitous in berries, and also the metabolic source of all other aromatic compound production in plants via the shikimate pathway (Pero 2010a); e.g.…”
Section: Scientific Historymentioning
confidence: 99%
“…It is important to remember that quinic acid is a natural-occurring alpha hydroxy organic acid quite ubiquitous in berries, and also the metabolic source of all other aromatic compound production in plants via the shikimate pathway (Pero 2010a); e.g. the bioactive agents in berries such as hydroxy organic acids (hydroxy benzoic, hydroxy cinnamonic and caffeic acids), flavinoids, and ellagic acid (Stoner et al 2008). The progression of events that established Cat's Claw extracts as the most consistent and potent DNA repair enhancer of anti-aging effects has become obvious, and signaled why some elements are built of the knowledge of the later events that have happened, to paint a more complete picture of how DNA repair regulates aging.…”
Section: Scientific Historymentioning
confidence: 99%